Analisis Pengendalian Persediaan Bahan Baku Biji Plastik Dengan Metode Probabilistik Di UD. ACC Plastik Sememi, Benowo, Surabaya - Ahmad Syifa’ul Qulub; Erni Puspanantasari Putri (Pusat Riset dan Inovasi Nasional, 2023)
UD ACC Plastics is a business in the field of plastic products that are produced, namely Hangers made from PP (polypropylene) plastic. Planning and controlling raw materials is very important for plastic companies with manual cupola especially UD. ACC Plastic. Fluctuating demand from customers resulted in excess and shortage of raw materials at UD. ACC Plastic. For that we need a definite and optimal calculation. In this case, an analysis of the planning and control of raw materials is carried out using the probabilistic method of the P Back Order model. To find out the order time interval, safety stock, lot order size, and inventory costs. Inventory and Control is done by probabilistic calculation of the P Back Order model with the Hadley Within solution by doing iterations and selecting the best solution with the minimum total inventory cost. Calculation results obtained total minimum inventory costs and optimal inventory system. In the raw material inventory of plastic pellets, the total cost of Rp. 204,325,752 with order intervals every 23 days or 0.062 years, order lot sizes of 415 kg, safety stock of 134.59 kg and a maximum order of 550 kg. The service level provided was 99.96%.